Human societies : a brief introduction - Sutton, Mark Q. (New York, NY : Routledge Taylor & Francis Group, 2025)
"Human Societies: A Brief Introduction succinctly covers the basic concepts of Cultural Anthropology in a way that is relevant and engaging to the introductory student. Less time is spent on anthropological detail and more time on the relevance of anthropological understanding to the contemporary world. The issues facing the contemporary Western world are also faced by the thousands of other societies. The book deals with topics such as the variety of sexualities, the thousands of religions, how people adapt to their environments, the ways people organize themselves, the multitude of foods and cuisines, adaptations to climate change, refugees and migrants, and the many different approaches to reproduction; all topics to which students should already be generally aware. Included are succinct chapters discussing personality, adaptation, social, political, and economic organization, food and diet, sex and gender, religion and ritual, and change and development. The book also includes short "Spotlight" boxes that enlighten the reader about specific topics of interest, as well as chapter summaries, exercises, key terms, and a comprehensive glossary. Human Societies: A Brief Introduction is essential reading for undergraduate students making their first steps into Cultural and Applied Anthropology"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Anthropology; Social history; Ethnology -- History; Sociolinguistics; Medical anthropology